Is Europe Overbanked? - Marco Pagano; Sam Langfield; Viral V. Acharya; Arnoud Boot; Markus K. Brunnermeier; Claudia Buch; Martin F. Hellwig; André Sapir; Ieke van den Burg (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2014)
Banking has grown too much in Europe - in three senses. First, the European banking system has reached a size where its contribution to real economic growth is likely to be nil or negative. Second, the European financial structure is biased towards banks (rather than securities markets), which results in excessively volatile credit creation and lower economic growth. Third, large universal banks - which perform a wide range of banking services, and are peculiarly common in Europe - contribute more to systemic risk than small and narrowly focused banks. To deal with these problems, policymakers should consider new measures such as aggressive anti-trust policy, structural reform of the banking sector, and a capital markets union to address Europe's overbanking problem.
Keywords: G10; G20; 330; banks; financial structure; systemic risk; universal banks; bank regulation